Effects of lipid packing and intermolecular hydrogen bond on thermotropic phase transition of stearyl glucoside - Ishak, Khairul Anwar; Zahid, Noor Idayu Mat; Velayutham, Thamil Selvi; Annuar, Mohamad Suffian Mohamad; Hashim, Rauzah (Elsevier, 2019)
The sugar anomeric effect on the thermotropic phase transition of stearyl glucoside was investigated. Standard analysis to study the phase transition through differential scanning calorimetry (DSC), and optical polarizing microscopy (OPM) was applied. In addition, small- and wide-angle X-ray scattering (SWAXS) and impedance spectroscopy (IS) were used to elucidate the phase structural information and the dielectric response of the glycolipid self-assembly system, respectively. A distinctive solid-to-liquid crystal phase transition of α- and β-stearyl glucoside was observed. At ambient temperature we observed semi-crystalline structure for the former and gel phase for the latter. α-Stearyl glucoside showed only one-step transition from semi-crystal to lamellar liquid crystal phase. In contrast, the gel phase of β-stearyl glucoside showed several distinct transition states prior to lamellar liquid crystal phase. Here the underlying reason for the observed β-stearyl glucoside polymorphism possibly involved strong intermolecular interaction originating from the combination of interlayer H-bonding and intralayer van der Waals forces. © 2019 Elsevier B.V.